2021
DOI: 10.1111/aos.14773
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the choroid on the onset and development of myopia: from perspectives of choroidal thickness and blood flow

Abstract: Myopia is the most common type of refractive errors characterized by excessive elongation of the ocular globe. With the increasing prevalence of myopia, improved knowledge of factors involved in myopia development is of particular importance. There are growing evidence suggesting that the choroid plays an important role in the regulation of eye growth and the development of myopia. Studies have demonstrated that thinning choroid is a structural feature of myopia, with a negative correlation between choroidal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 137 publications
(164 reference statements)
7
61
0
Order By: Relevance
“…Alternatively, a detailed, comprehensive assessment of the choroidal vasculature and choriocapillaris perfusion might be more informative. 46,47 Studies with animal models in which myopia is induced by unilateral manipulation of visual inputs have established that alteration in ChT is an early sign of vision-driven changes in ocular growth and myopia development. [13][14][15] The ChT responds to visual stimuli in a bidirectional, rapid, and regionally selective manner.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a detailed, comprehensive assessment of the choroidal vasculature and choriocapillaris perfusion might be more informative. 46,47 Studies with animal models in which myopia is induced by unilateral manipulation of visual inputs have established that alteration in ChT is an early sign of vision-driven changes in ocular growth and myopia development. [13][14][15] The ChT responds to visual stimuli in a bidirectional, rapid, and regionally selective manner.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient supply of the choroid mainly comes from the short-posterior ciliary artery. As one of the most highly vascularized tissues of the body, the choroid accounts for 65% of the blood supply within the eye; hence, it is reasonable to assume that the progression of pathological myopia is linked to the structural and functional alterations of the choroid (5,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient supply of the choroid mainly comes from the short-posterior ciliary artery. As one of the most highly vascularized tissues of the body, the choroid accounts for 65% of the blood supply within the eye; hence, it is reasonable to assume that the progression of pathological myopia is linked to the structural and functional alterations of the choroid ( 5 , 24 26 ). Studies have shown that CT alterations occurred earlier than the fundus changes and that visual function abnormalities occurred in the early stage of pathologic myopia ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“… 66 Hence, choroidal thinning was supposed to serve as a new target or predictor biomarker for myopic development and progression. 67 , 68 …”
Section: Choroidal Response To Iopmentioning
confidence: 99%